Distribution of trace elements in groundwater around Beris Lalang landfill Bachok, Kelantan, Malaysia - Mohammad Muqtada Ali Khan; Hafzan Eva Mansor; Nur Hanis Aflatoon; Kishan Raj Pillai, Mathialagan (IOS Press, 2017)
The present study was conducted in the vicinity of Beris Lalang landfill, part of state Kelantan, Malaysia to determine the distribution of trace elements concentration in groundwater. A total of eleven groundwater samples and two surface water samples were analyzed for lead (Pb), manganese (Mn), copper (Cu), zinc (Zn), iron (Fe), chromium (Cr) and aluminium (Al) using Atomic Absorption Spectrophotometer (AAS). These probe elements were further categorized as toxic metals (i.e. Pb), transition metals (i.e. Mn), metallic elements (i.e. Cu, Fe, Zn, Cr), and non-metallic elements (i.e. Al). This study shows that few groundwater samples have marginally high concentration of Mn, Pb, Fe and Cr as per W.H.O. standard for potable water. The high concentration of metal ions in groundwater is likely due to untreated effluents from landfill site, municipal wastewater, fertilizers and other activities. To help identifying the contamination sources, the study recommends that regular monitoring of the groundwater quality should be undertaken both temporally and spatially that can contribute in public health and as well agricultural uses.